Examining relationships between children's sex, cognitive development, executive functioning, and home learning environment - Gogan, Amber (My University, 2026)
Executive function (EF) refers to cognitive processes that support goal-directed behaviour, including inhibitory control, working memory, and cognitive flexibility. These abilities are closely linked to early learning and cognitive development. One common measure of EF in early childhood is the Head–Toes-Knees-Shoulders Task (HTKS) task, which requires children to remember rules and inhibit dominant responses. Although EF has been associated with general cognitive ability, less is known about how it relates to specific domains of intelligence or whether sex differences are present in early childhood. This study examined sex differences in executive and cognitive functioning and explored associations between EF, cognitive abilities, and aspects of the home environment. Participants included 70 children aged 3–6 years. Children completed the Wechsler Preschool and Primary Scale of Intelligence–Fourth Edition (WPPSI-IV) and the HTKS task, while parents completed questionnaires about the home learning environment. Exploratory factor analysis identified three home environment factors: home literacy activities, play-based and experiential learning, and parental STEM attitudes. Spearman’s partial correlations showed that EF is robustly tied to general cognitive ability as measured by the WPPSI-IV indices, with the exception of working memory (ρ = 0.175, p = 0.148). Forward regression analyses indicated that visual-spatial ability and processing speed contribute to executive function performance. These findings suggest that EF in early childhood is closely related to specific cognitive abilities. The home environment factors did not contribute significantly to the model but may moderate the relationship between cognitive ability and executive functioning.
Presented on April 23, 2026, at Student Research Day, held at MacEwan University in Edmonton, AB.
Keywords: executive function (EF); Wechsler Preschool and Primary Scale of Intelligence-Fourth Edition (WPPSI-IV); Head-Toe-Knees-Shoulders Task (HTKS); cognitive abilities; Student Research Day